EFEKTIVITAS TERAPI KOMPLEMENTER UNTUK MENINGKATKAN KUALITAS HIDUP PADA PASIEN KANKER: LITERATURE REVIEW: Effectiveness of complementary therapies to improve quality of life in cancer patients: a literature review - Siti Utami; anggi pratiwi; ayu muthia (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Cancer has been known as a disease that has a serious impact on the body and the sufferer's psychology. Quality of life, as well as anxiety about the state of the body, psychology, body image disturbances, and signs of symptoms that can cause distress, should immediately improve the quality of life of cancer sufferers. As nurses, we must provide a complementary-based therapeutic intervention that can help improve a person's quality of life. The purpose of this literature review is to determine the effectiveness of the application of complementary therapies to improve the quality of life of cancer patients. This research is in the form of a literature review of articles collected using the ProQuest, ScienceDirect, and PubMed databases with the keywords complementary therapy, quality of life, and cancer patients. Inclusion criteria include articles published from 2013–2023. Based on a review of 11 articles discussing the application of complementary therapy interventions that can provide effective results to improve the quality of life for cancer patients, complementary therapy has a significant impact on improving the quality of life of cancer patients and can be used as an alternative intervention to improve their quality of life